Expression analysis, single-nucleotide polymorphisms of the Myoz1 gene and their association with carcase and meat quality traits in chickens. Issue 4 (2nd October 2018) - Luo, Bin; Ye, Maosen; Xu, Hengyong; Ma, Enyue; Ye, Fei; Cui, Can; Zhu, Qing; Zhao, Xiaoling; Yin, Huadong; Diyan, Li; Qiu, Mohan; Yang, Chaowu; et al.
Abstract: Previous studies reported that the Myoz1 gene plays a crucial role in signal transduction and muscle fibre type differentiation. This finding suggests that the Myoz1 gene is a potential candidate for affecting carcase and meat quality traits in animals. Therefore, this study aimed to detect genetic variations in Avian and Yellow Bantam chickens and to evaluate the effects of these variations on economically important carcase and meat-quality traits. Expression analysis using quantitative real-time PCR indicated that Myoz1 was broadly expressed in all four studied tissues (liver, heart, breast muscle and leg muscle). Expression of Myoz1 was significantly higher in both leg muscle and breast muscle compared to the liver and heart. Then, using direct sequencing, a total of five single nucleotide polymorphisms (SNPs) were identified within the Myoz1 gene in two breeds of chickens. These breeds included three non-synonymous SNPs (SNP1: g. 16022512 G > T, SNP3: g. 16022560 C > T and SNP5: g.16023903 A > G) corresponding to A103S, H119Y and S189G, respectively. Statistical analyses indicated that SNP2 (g. 16022529 T > C), SNP3, SNP4 (g.16023878 A > C) and SNP5 significantly influenced some carcase and meat quality traits. Meanwhile, we did not find any association between the constructed haplotype and carcase traits in the Avian nor Yellow Bantam chickens. In conclusion, SNPs in the Myoz1 gene could be used for marker-assisted selection in chicken breeding.